2013
DOI: 10.1016/j.carbpol.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of polysaccharide obtained from red seaweed Gracilaria caudata (J Agardh)

Abstract: Seaweeds are considered an important source of bioactive molecules. In this work the marine red alga Gracilaria caudata was submitted to aqueous extraction of their polysaccharides for 2 h at 100 °C. The polysaccharide fraction (PGC) presented a recovery of 32.8%. The sulfate content of PGC, calculated by S%, is 1 ± 0.2% and the degree of sulfation accounts for 0.13 ± 0.2. High-Performance Size-Exclusion Chromatography demonstrated that PGC consists of a high molecular weight polysaccharide (2.5 × 10(5)gmol(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 62 publications
4
65
1
3
Order By: Relevance
“…Furthermore, spectral data revealed signals representative of 2-O-CH 3 , 6-SO 3 -and 6-unsubstituted from 1 H-2 and 13 C-2 pairs due to a methyl-esterified site showing methylation pattern possibly attached to O-6 of D-galactose (Duarte et al, 2004;Barros et al, 2013;Quinderé et al, 2014), as was also previously suggested ( Figures 1A, B and C). It has been widely described the degree of substitution of methyl ether at C-6 varying among species (Cardozo et al, 2007;Maciel et al, 2008: Prajapati et al, 2014.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, spectral data revealed signals representative of 2-O-CH 3 , 6-SO 3 -and 6-unsubstituted from 1 H-2 and 13 C-2 pairs due to a methyl-esterified site showing methylation pattern possibly attached to O-6 of D-galactose (Duarte et al, 2004;Barros et al, 2013;Quinderé et al, 2014), as was also previously suggested ( Figures 1A, B and C). It has been widely described the degree of substitution of methyl ether at C-6 varying among species (Cardozo et al, 2007;Maciel et al, 2008: Prajapati et al, 2014.…”
Section: Resultssupporting
confidence: 85%
“…Due to the association between the intensity signals attributed to methyl hydrogens (around δ H 1.4-1.6 ppm) and the L-galactose residue (δ H 5.3 ppm), it was denoted in this study the presence of pyruvated (Pyr)-D-galactose residues in the 1 H-13 C edited-HSQC spectral value of A. muscoides galactans based on Barros et al (2013), and this structural feature was in accordance to the Acanthophora genus (Duarte et al, 2004), consistent with 1 H NMR spectral data ( Figures 1A, B and C), since pyruvic acid has not been frequently found in agarophytes (Cardozo et al, 2007). Furthermore, spectral data revealed signals representative of 2-O-CH 3 , 6-SO 3 -and 6-unsubstituted from 1 H-2 and 13 C-2 pairs due to a methyl-esterified site showing methylation pattern possibly attached to O-6 of D-galactose (Duarte et al, 2004;Barros et al, 2013;Quinderé et al, 2014), as was also previously suggested ( Figures 1A, B and C).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These polysaccharides mainly consist of small sugar units linked via glycosidic bonds, which have hydrophilic surface groups such as carboxyl, hydroxyl, and sulfate groups [80]. Typical polysaccharides found in seaweeds include agar, alginate, carrageenan, fucoidan, and laminarin [81]. Other biomolecules found in the cell walls include proteins and enzymes.…”
Section: Biosynthesis Of Nanoparticlesmentioning
confidence: 99%